Toxicological Review of Anticancer Plants Used in Traditional Medicine in Morocco - Soufiane Drioua; Abha Cherkani-Hassani; Otman El-Guourrami; Mouna Ameggouz; Ahmed Zahidi; Abdelhakim Bouyahaya; Sayyed Ibrahim Shah; Yaser Mohammed Al-Worafi; Long Chiau Ming; Hanane Benzaied; Anass Doukkali (Progress in Microbes and Molecular Biology)
In Morocco, traditional medicine utilizes many toxic plants for cancer treatment, despite a lack of scientific evidence supporting their effectiveness. Further research may be able to explore and discover the potential therapeutic effects of these plants' bioactive molecules with antioxidant and anticancer properties. Based on our review, we have determined that the 13 plants under examination possess various pharmacological and biological activities due to their diverse phytochemical composition. Despite their toxicity, these plants have a history of traditional use in Morocco for treating multiple diseases. Further research, including preclinical and clinical trials, should be conducted to investigate the potential therapeutic benefits of these plants. Moroccan cuisine commonly incorporates gruels, herbal drinks, and spicy beverages, which possess significant health benefits, including chemo-preventive properties and natural inhibitors against certain infections. These properties may aid in reducing the incidence of cancer and potentially have therapeutic effects in various human pathologies when consumed in appropriate amounts and in combination with a healthy lifestyle.